The supermarket revolution and food security in Namibia - Nickanor, Ndeyapo; Kazembe, Lawrence; Crush, Jonathan Scott 1953-; Wagner, Jeremy (Urban food security series, 2017)
The surprisingly high rate of supermarket patronage in low-income areas of Windhoek, Namibia's capital and largest city, is at odds with conventional wisdom that supermarkets in African cities are primarily patronized by middle and high-income residents and therefore target their neighbourhoods. What is happening in Namibia and other Southern African countries that make supermarkets so much more accessible to the urban poor? What are they buying at supermarkets and how frequently do they shop there? Further, what is the impact of supermarket expansion on informal food vendors? This report, which presents the findings from the South African Supermarkets in Growing African Cities project research in 2016-2017 in Windhoek, looks at the evidence and tries to answer these questions and others. The research and policy debate on the relationship between the supermarket revo- lution and food security is also discussed. Here, the issues include whether supermarket supply chains and procurement practices miti- gate rural food insecurity through providing new market opportunities for smallholder farmers; the impact of supermarkets on the food security and consumption patterns of residents of African cities; and the relationship between supermarket expansion and governance of the food system, particularly at the local level.